Pengaruh Ion Logam Cu(II) Terhadap Persen Ekstraksi Ion Pb(II) Menggunakan Teknik Emulsi Membran Cair - Irawati, Dwi Ardi; Hamzah, Baharuddin; Rahman, Nurdin (Jurnal Akademika Kimia, 2016)
This study aimed to determine effect of Cu(II) ion toward percent extraction of Pb(II) ion using emulsion liquid membrane technique. Variation concentrations of Cu(II) added were 0, 50, 100, 150, 200 and 250 ppm with the initial concentration of Pb(II) was 245 ppm. This extraction used benzoyl acetone as a chelating agent. The extraction results were measured by Spectrodirect. The results showed that percent extraction of Pb(II) ion prior addition of Cu(II) ion was 99.09%, but after addition of Cu(II) to a concentration up to 250 ppm, the percent extraction of Pb(II) ions turned to decrease by 97.92%.